Congenital diaphragmatic hernia: what are the priorities for the next 20 years? - McCulley, David; Kipfmüller, Florian; Patel, Neil (Seminars in fetal & neonatal medicine, 2025)
Advances in clinical care, biomedical research, and health advocacy have significantly improved survival and quality of life across the lifespan. To sustain and accelerate this progress, it is essential to define clear goals for the future. Congenital diaphragmatic hernia (CDH), one of the most common and severe congenital malformations, serves as a model condition where coordinated efforts in clinical care, research, and advocacy have led to important advances in understanding disease mechanisms and improving outcomes. Reflecting on this progress reveals several key themes, including the value of disease modelling, novel therapeutic strategies, and sustained innovation. Achieving a better future for people with CDH will require strategic prioritization of research, engagement of methodological expertise, addressing practical barriers, and promotion of collaboration. We propose that coordinated global efforts - including for example the creation of an international research platform, leveraging technological advances, and raising the visibility of CDH - will empower clinicians, researchers, and the CDH community to drive continued progress.
Online verfügbar: 26. August 2025, Artikelversion: 16. Oktober 2025
Gesehen am 03.12.2025